2008
DOI: 10.1007/s00534-007-1208-7
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous double cancer of the gallbladder and pancreas associated with pancreaticobiliary maljunction

Abstract: A 50-year-old Japanese woman complained of abdominal and back pain. Ten years previously she had undergone cholecystectomy, choledochectomy, and Roux-en-Y choledochojejunostomy for gallbladder cancer associated with pancreaticobiliary maljunction without bile duct dilatation. On the present admission, ultrasonography (US) and computed tomography (CT) demonstrated a large mass, 60 mm in size, in the pancreatic tail. Endoscopic retrograde cholangiopancreatography (ERCP) showed obstruction of the main pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Between 1957 and 2008, there were only 35 cases in which pancreatic cancer was reported in patients with PBM [99][100][101]. While the incidence of pancreatic cancer was reported to be 0.0162 % in the overall population in Japan, in patients with PBM this incidence reached 0.8 %, a 49.4-fold increase compared with that in the overall population [102].…”
Section: Commentsmentioning
confidence: 99%
“…Between 1957 and 2008, there were only 35 cases in which pancreatic cancer was reported in patients with PBM [99][100][101]. While the incidence of pancreatic cancer was reported to be 0.0162 % in the overall population in Japan, in patients with PBM this incidence reached 0.8 %, a 49.4-fold increase compared with that in the overall population [102].…”
Section: Commentsmentioning
confidence: 99%
“…However, the relationship between pancreatic cancer and PBM remains controversial and unclear. In addition, cases of double cancer of the biliary system and the pancreas is extremely rare in patients with PBM (8,(10)(11)(12), despite occasional reports of multiple cancers of the biliary system in patients with PBM (3)(4)(5). The present case suggested that careful attention should be paid to the whole pancreaticobiliary system with regard to carcinogenesis, however, further case studies are needed.…”
Section: Discussionmentioning
confidence: 67%
“…The definitive distinction between multicentric primary cancers and gallbladder cancer metastases is difficult. Although biliary cancer in patients with PBM is occasionally encountered, pancreatic cancers in patients with PBM are rare (8)(9)(10)(11)(12). Funabiki et al (13) reported that the incidence of pancreatic cancer is higher in patients with PBM than in patients without PBM.…”
Section: Discussionmentioning
confidence: 99%
“…Multifocal cancer of the biliary tree and pancreas associated with pancreaticobiliary maljunction has been reported in 7 patients (two cases were triple cancer of the gallbladder, the bile duct and the pancreas) [46] and six of them were women. In the seven patients, the cancer of the gallbladder occurred previously or synchronously with the pancreatic cancer [7] . Gallbladder cancer was more frequent than bile duct cancer [7] .…”
Section: Discussionmentioning
confidence: 99%
“…In the seven patients, the cancer of the gallbladder occurred previously or synchronously with the pancreatic cancer [7] . Gallbladder cancer was more frequent than bile duct cancer [7] . Three patients had bile duct dilatation and none presented a choledochal cyst.…”
Section: Discussionmentioning
confidence: 99%